2016
DOI: 10.1002/job.2105
|View full text |Cite
|
Sign up to set email alerts
|

Daily shifts in regulatory focus: The influence of work events and implications for employee well‐being

Abstract: Summary Although theory suggests that regulatory focus fluctuates within person and such fluctuations impact employee well‐being, there is little empirical investigation of such propositions. These are important research questions to address because work events may elicit within‐person fluctuations in regulatory focus, which can then affect well‐being. The primary purpose of this study is to examine specific predictors of daily regulatory focus at work and the foci's impact on employee well‐being at work and h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
76
2
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 82 publications
(96 citation statements)
references
References 96 publications
6
76
2
1
Order By: Relevance
“…But the opposite may also be true: Interventions intended to build resources might be most helpful for employees with poor‐quality LMX relationships because their supervisory relationship provides fewer naturally occurring resource‐building interactions. This prediction is consistent with a recent study that found stronger effects of positive events for employees with low‐quality LMX relationships than for those with high‐quality LMX (Koopmann, Lanaj, Bono, & Campana, ).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…But the opposite may also be true: Interventions intended to build resources might be most helpful for employees with poor‐quality LMX relationships because their supervisory relationship provides fewer naturally occurring resource‐building interactions. This prediction is consistent with a recent study that found stronger effects of positive events for employees with low‐quality LMX relationships than for those with high‐quality LMX (Koopmann, Lanaj, Bono, & Campana, ).…”
Section: Discussionsupporting
confidence: 92%
“…Feicht et al In addition to the effects that might arise from the organizational context itself, unique group dynamics and existing work relationships might also shape the results of interventions in complex ways. For example, given evidence that partner reactions are critical for the effectiveness of social sharing (e.g., Gable et al, 2004) is extreme pressure to perform and little concern for worker well- recent study that found stronger effects of positive events for employees with low-quality LMX relationships than for those with high-quality LMX (Koopmann, Lanaj, Bono, & Campana, 2016).…”
Section: Future Research Directionsmentioning
confidence: 99%
“…In the second part of the path, a promotion focus also had a positive effect on emotional well-being. This result is consistent with the results of previous research that a promotion focus led to emotional well-being (Brunstein et al, 1998;Koopmann et al, 2016;Lichtenthaler & Fischbach, 2019). Taken together, this finding implies that a promotion focus resulting from a calling toward teaching causes emotional well-being.…”
Section: Discussionsupporting
confidence: 92%
“…Consistent with the above perspective, some evidence demonstrated that a promotion focus relates to higher emotional well-being than prevention focus (Koopmann, Lanaj, Bono, & Campana, 2016;Lichtenthaler & Fischbach, 2019). For example, Koopmann et al (2016) showed that promotion focus was linked to higher emotional well-being, whereas prevention focus was linked to lower emotional well-being. In the research, especially, it is worth noting that emotional well-being was the highest when the promotion focus was high while the prevention focus was low.…”
Section: Introductionmentioning
confidence: 81%
See 1 more Smart Citation